MILITARY STRATEGIC AND OPERATIONAL ART OF MASTER AMIR TEMUR (American Journal of Pedagogical and Educational Research, 2023)
The article describes Amir Temur’s military strategy, operations and tactics, which he used in his military art to found a great state in the field of history, as well as the enormous potential, skills, knowledge and experience of the founders.